Western intellectual culture and predisposition of U.S.-Israel foreign policy on muslim political riddles - Shuriye, Abdi Omar (Institute Of Diplomacy and Foreign Relations, 2004)
The destructive image of lslam is becoming more inherent in the western perception not only from the increasingly inaccurate media coverage but also the cultural propensity that extremely flouts the crux of lslam on the part of the western sphere; academics, media and laymen in the west adhere to the same terminological attitudinal tendency, the media creates distorted picture, the academics supply the justifications and authenticate the image and the unsuspecting audiences, the society, make use of it to further arraign the massage of the last religion in a spectrum of misconceptions. The repeated motion pictures on the screens are the irrevocable guru of today's western public. The purpose of this paper is to explore the raison d'6tre of the traumatic patent of inaccuracy and evasively deviousness on the part of the western hemisphere on lslam and Muslims. The war on carnage has come to resemble a war on lslam and Muslims, since 9/11th we have witnessed Muslims becoming under constant assault although the western establishments argue that the war is not a war against religion or against the Muslim faith rather against individual militants. The paper studies the foreign policy of the U.S. towards Islam and Muslims after 9/11th avoiding poignancies and employing sagaciousness as its core method. The West seem identified a new enemy or extensive discourse between the East and the West of sharing common worldview as far as religion remained common ground for values. However, with the European nonessentialisation of religion this reciprocal affiliate petered out and subsequently the two plunge into an opposite paradigms. From here onwards, the West developed new civilisation and political outlook on Islam and Muslims. Prophet Mohamed’s flexibility and peace treatises with the Christians and Pagans had elapsed, and a latecomer conception on non-coexist-ability of Muslims on non-Muslims for religion grounds, a notion based upon fictitious premises, replaces it.